Spray‐Drying and Atomic Layer Deposition: Complementary Tools toward Fully Orthogonal Control of Bulk Composition and Surface Identity of Multifunctional Supraparticles (Small Methods 1/2022). Issue 1 (18th January 2022) - Müssig, Stephan; Koch, Vanessa M.; Collados Cuadrado, Carlos; Bachmann, Julien; Thommes, Matthias; Barr, Maïssa K. S.; Mandel, Karl
Abstract : Inside Back Cover In article number 2101296, Thommes, Barr, Mandel, and co‐workers used spray‐drying as a scalable process that enables one to assemble freely chosen nanoparticles into supraparticles, i.e., microparticles with adjustable nanostructure, in combination with atomic layer deposition to deposit controlled thin films of different materials onto and within supraparticles. The combination of these two techniques allows for the independent adjustment of properties determined by bulk and surface composition.